Formation of Soviet Postgraduate Studies in History in USSR in 1930s: Legislative Regulation and Practice - A. M. Skvortsov (Научный диалог, 2021)
The formation of the institute of postgraduate studies in history in the USSR in the 1930s is examined in the article. The sources used are published legislative acts, journalistic materials, archival data. The relevance of the study is due to the fact that the proposed problem was often considered in the context of the history of scientific and scientific and educational institutions or exclusively through regulatory legal acts without taking into account the practice that actually existed and developed under the influence of the community of scientists. Using the materials of curricula for the training of graduate students of Moscow University, Leningrad University, the Institute of History of the Academy of Sciences of the USSR, as well as using the individual plans of graduate students, the author proves that the older generation of historians sought to integrate pre-revolutionary standards and mechanisms for training dissertation candidates into the new conditions of Soviet power. It is stated in the article that, despite the publication of numerous decrees, instructions, rules by government structures in relation to the institute of graduate school in the 1930s, there were no clear recommendations on the nature of the process of training scientific personnel. Supervisors of post graduate students, as a rule, themselves determined the scope of requirements for applicants. The author reveals the relative freedom of historians in determining the conditions and scientific criteria for entering the scientific community of neophytes.